Odpowiedzi

2009-12-17T19:48:25+01:00
C
x-2y=3
-2x-y=o

x=3-2y

-2(2-2y)=0
-4+4y=o
4y=4
y=1 x=1
y=1

x=3-2*1
x=3-2
x=1


d
2x-y=9
5x-4y=3

-y=9-2x /*-1
y=-9+2x

5x-4(-9+2x)=3
5x+36-8x=3
-3x=-33
x=11 x=11
y=13

y=-9+22
y=13

e
3x-2y=5
2x-y=4

-y=4-2x
y=-4+2x

3x-2(-4+2x)=5
3x+8-4x=5
-x=-3
x=3 x=3
y=2

y=-4+2*3
y=-4+6
y=2

f
2x+9y=-9
-3x+3y=8

2x=-9-9y /:2
x=-4,5-4,5y


-3(-4,5-4,4y)+3y=8
13,5+13,5y+3y=8
16,5y=-5,5
y=0,3 x=-5,85
y=0,3

x=-4,5-4,5*0,3
x=-5,85


g
2x+3y=3
8x-5y=-1

2x=3-3y
x=1,5-1,5y

8(1,5-1,5y)-5y=-1
12-12y-5y=-1
-17y=-13
y=0,76 x=0,36
y=0,76

x=1,5-1,5*0,76
x=1,5-1,14
x=0,36
2009-12-17T20:02:00+01:00
C){x-2y=3
{-2x=y=0

{-2y=3-x
{-2x-3-x=0
{-2y=3-x
{-3x=3 / (-3)

{-2y=3-x
{x=-1

{-2y=3-(-1)
{x=-1

{-2y=4 /(-2)
{x=-1

{y=-2
{x=-1

d){2x-y=9
{5x-4y=3


{2x-y=9
{-4y=3-5x

{2x-3-5x=9
{-4y=3-5x

{-3x=12 /(-3)
{-4y=3-5x

{x=-4
{-4y=3-(-20)

{x=-4
{y=-5,75

reszty nie wiem